Penegakan Hukum Pendaftaran Diri Sebagai Pengusaha Kena Pajak - Aziz, Moch. Ayub Abdul; Purwaningsih, Sri Budi (Web of Scientist International Scientific Research Journal, 2023)
In law enforcement in the field of taxation, especially in registration as a taxable entrepreneur in Indonesia, especially in the Sidoarjo area, it is felt that it is not optimal and it can still be found some entrepreneurs who have not registered themselves as entrepreneurs, why do taxes come from a lack of understanding of taxation on the part of the entrepreneur or abuse or disobedience by the entrepreneur? the entrepreneur, here the author conducts research at a kpp madya Sidoarjo to collect data and examine data from entrepreneurs who are registered but do not have the status of a taxable entrepreneur to the imposition of sanctions on business actors who violate. from the results of research conducted by the author found several kinds of cases in the registration of taxable entrepreneurs. From the conclusion, the author's findings are still considered less than optimal in law enforcement to entrepreneurs who violate so that there are still many entrepreneurs who commit violations.